Violence against Women with Chronic Maternal Disabilities in Rural Bangladesh (Journal of Health, Population and Nutrition, 2012)
This study explored violence against women with chronic maternal disabilities in rural Bangladesh. During  November 2006July 2008, in-depth interviews were conducted with 17 rural Bangladeshi women  suffering from uterine prolapse, stress incontinence, or fistula. Results of interviews showed that exposure  to emotional abuse was almost universal, and most women were sexually abused. The common triggers  for violence were the inability of the woman to perform household chores and to satisfy her husbands  sexual demands. Misconceptions relating to the causes of these disabilities and the inability of the affected  women to fulfill gender role expectations fostered stigma. Emotional and sexual violence increased their  vulnerability, highlighting the lack of life options outside marriage and silencing most of them into accepting  the violence. Initiatives need to be developed to address misperceptions regarding the causes of such  disabilities and, in the long-term, create economic opportunities for reducing the dependence of women  on marriage and men and transform the society to overcome rigid gender norms.   DOI: http://dx.doi.org/10.3329/jhpn.v30i2.11312   J HEALTH POPUL NUTR 2012 Jun;30(2):181-192